Automated model to rank candidates for a job position based on data extracted from LinkedIn profiles - Nadia, Mouri Hoque (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.